2003
DOI: 10.1161/01.res.0000085041.70276.3d
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Functional Identification of Cyclic AMP-Sensitive BK Ca Potassium Channels (ZERO Variant) and L-Type Voltage-Dependent Calcium Channels in Single Rat Juxtaglomerular Cells

Abstract: Abstract-This study aimed at identifying the type and functional significance of potassium channels and voltagedependent calcium channels (Ca v ) in single rat JG cells using whole-cell patch clamp. Single JG cells displayed outward rectification at positive membrane potentials and limited net currents between Ϫ60 and Ϫ10 mV. Blockade of K ϩ channels with TEA inhibited 83% of the current at ϩ105 mV. Inhibition of K V channels with 4-AP inhibited 21% of the current. Blockade of calcium-sensitive voltage-gated K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 27 publications
1
54
1
Order By: Relevance
“…PGE 2 and PGI 2 are likely candidates that activate cAMP-coupled EP2, EP4, and IP receptors on JG cells and enhance potassium current carried through the cAMP-sensitive "zero" variant of the calcium-sensitive voltage-activated potassium (BK Ca ) channels. 11,12 The data presented here show that cAMP/PKA is crucial for transduction of the hypotonicity-induced renin secretory and current response. In agreement with this finding, renin release after a hypotonic challenge is not additive to the response elicited by intracellular application of cAMP.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…PGE 2 and PGI 2 are likely candidates that activate cAMP-coupled EP2, EP4, and IP receptors on JG cells and enhance potassium current carried through the cAMP-sensitive "zero" variant of the calcium-sensitive voltage-activated potassium (BK Ca ) channels. 11,12 The data presented here show that cAMP/PKA is crucial for transduction of the hypotonicity-induced renin secretory and current response. In agreement with this finding, renin release after a hypotonic challenge is not additive to the response elicited by intracellular application of cAMP.…”
Section: Discussionmentioning
confidence: 73%
“…Depolarization of the JG cell membrane potential activates voltage-gated calcium channels and calcium influx, which inhibits cAMP-mediated exocytosis of renin. 12 We have shown that hyperpolarization indirectly supports exocytosis of renin by stabilizing membrane voltage in a range far from threshold for calcium channel activation and thus inhibition of renin release. 12 The series of events between a hypotonic challenge and COX-2 activity in JG cells is likely to include cell swelling and PLA 2 activation as observed in several cell types.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Nonspecific binding was blocked with TBST and 5% BSA for 30 minutes. The cells were washed and then incubated for 1 hour with a primary antibody against mouse renin 18 (Swant, Bellinzona, Switzerland), diluted 1:50 in 5% BSA in TBST. Cells were washed and incubated with a goat anti-mouse secondary antibody labeled with Alexa Fluor 488 green fluorescent dye (Alexa Fluor, Invitrogen) diluted 1:100 in 5% BSA in TBST for 1 hour.…”
Section: Immunolabeling Of Cultured Jg Cellsmentioning
confidence: 99%
“…In addition, stimulation by isoproterenol + IBMX left membrane potential unaltered at approx. -60 mV (see also Bührle et al 1986) but is at variance with the hyperpolarisation observed by Fishman (1976) and Friis et al (2003).…”
Section: Mechanistic Considerationsmentioning
confidence: 50%